Comparison of aerobic and muscular power between junior/U23 slalom and sprint paddlers: An analysis of international medalists and non-medalists - Bielik, V.; Lendvorský, L.; Vajda, M.; Lopata, P.; Ružbarský, P.; Masselli dos Reis, I. G.; Dalcheco Messias, L. H. (Frontiers in Physiology, 2021)
This study aimed to compare the aerobic power (treadmill running) and muscle power (bench press and bench pull) of Junior/U23 paddlers from Slovakia who won medals in international championships with that of those who did not take the podium. Forty-three Slovak Junior/U23 paddlers (sprint = 24, medalists = 8, non-medalists = 16; slalom = 19, medalists = 11, non-medalists = 8) were tested in 2018 and 2019 after the world championships. The maximal oxygen uptake (VO2max) and the velocity at maximal oxygen uptake (vVO2max) were determined by the incremental running protocol (0% slope and 1 km·h-1 increments every minute until volitional exhaustion). Mean maximal power from the entire concentric phase was recorded during bench press and bench pull exercises by the validated TENDO weightlifting analyzer. No interaction was obtained between medal and canoe discipline for VO2max (p = 0.069, F = 3.495), vVO2max (p = 0.552, F = 0.361) and absolute (bench press: p = 0.486, F = 0.495; bench pull: p = 0.429, F = 0.640) or relative (bench press: p = 0.767, F = 0.089; bench pull: p = 0.696, F = 0.155) mean maximal power. Conversely, a significant effect for the medal on the bench press (absolute p = 0.017, F = 6.170; relative p = 0.043, F = 4.384) and the bench pull (absolute p = 0.041, F = 4.470) mean maximal power were observed. Our study indicates the absolute mean power on the bench press as a prerequisite for success in international Junior/U23 championships of slalom and sprint canoeing. However, the mean power on bench pull seems to have a deeper influence on sprint paddlers when compared to slalom athletes. Regarding the aerobic power, the data from the treadmill testing did not reveal outcomes between medalists and non-medalists. This result can be associated with the lack of specificity of the incremental treadmill testing for canoeing, and future studies are encouraged to propose specific protocols to compare the aerobic power of medalists and non-medalists in international slalom and sprint championships.